The significance of breastfeeding on sleep patterns during the first 48 hours postpartum for first time mothers. (3rd April 2018) - Hughes, O.; Mohamad, M. M.; Doyle, P.; Burke, G.
Abstract: Postpartum women sleep less during the early days following delivery. Long-term sleep disturbance and fatigue can have significant implications for physical and mental health, relationships, employment and parental competence. Most studies focus on the quality and quantity of maternal sleep between weeks one and six postpartum. We explored sleep patterns and reasons for wakefulness of first-time mothers immediately following delivery. Thirty first-time mothers completed a postnatal sleep questionnaire, detailing their total sleep time (TST), the reasons for being awake and their level of fatigue. The logs were completed in real time during the first 48 h postpartum, while they were still in a hospital environment. The data collected from the mothers in the study indicated that the mean TST in the first 48 h was 9.7 h. Of the factors explored only breastfeeding influenced the TST. Breastfeeding women slept on average 2.6 h longer than women who bottle-fed ( p = .042). Impact statement: What is already known on this subject: Childbearing affects women's sleep in many ways. Hormonal changes during pregnancy and postpartum as well as physiological and anatomical alterations, and the process of adaptation to the new parent's responsibilities contribute to changes in sleep architecture. Since first study of sleep and pregnancy published in 1968 there have been very few publications addressing maternal sleep postpartum. Most studies which have focussed on quality of maternal sleep in the first 6-months postpartum period describe the relationships between poor maternal sleep and postpartum depression and other mental health outcomes. What the results of this study add: We explored sleep patterns and reasons for wakefulness of first-time mothers immediately following delivery while they remained in the hospital environment. We found that environmental factors such as background noise, shared rooms, type of delivery, feeding and worrying about the neonate did not influence the total sleep time, however, the main outcome of our study is that breastfeeding promotes maternal sleep. What the implications are of these findings for clinical practice and/or further research: We believe that this study would be of interest to many obstetricians, general practitioners, nurses and midwives as well as to the general public. Appropriate counselling of patients early in postnatal period can improve their sleep patterns and reduce the risk of depression and other abnormal physical, psychological and social outcomes.